Experimental study on the seismic behavior of large‐size square and rectangular steel reinforced concrete columns with high and normal strength concrete. (28th November 2021) - Yin, Fei; Wang, Ruwei; Cao, Wanlin; Dong, Hongying; Zhao, Yang; Song, Yu
Summary: To study the seismic behavior of steel reinforced concrete columns with various cross‐sectional shapes, steel shapes, and concrete strengths, four large‐size specimens were designed and an experimental study was conducted. High‐strength concrete can effectively improve the bearing capacity, stiffness, and energy dissipation capacity of proposed specimens, while the specimens with high‐strength concrete showed more serious compressive damage and lower ductility index. The square specimens showed more significant bearing capacity decline after the peak point than rectangular specimens and the ductility indexes were smaller. However, the ductility indexes and peak drift ratios of all specimens were larger than 3.58 and 1/50, which still met the suggested values in the related code. The ductility indexes and residual deformations of square specimens with high‐ and low‐strength concrete were more closed than those of rectangular specimens with high‐ and low‐strength concrete, indicating that the proposed square specimens had more stable deformation capacity under different concrete strength. Furthermore, considering the different confinement effects of concrete in different regions, the stress–strain relationships of concrete in different regions were calculated individually and a modified fiber‐based method was proposed. The calculated results showed good agreement with the experimental results, indicating that the method can be used for the design of steel reinforced concrete column cross‐sections.